PENGGUNAAN APLIKASI E-BANKING SELAMA PANDEMI COVID-19 PADA MAHASISWA UPNVJ - Al Faridzi Setyawan, (2021)
E-Banking is a digital product from the banking industry that is very innovative because it can provide convenience for both the customer, namely being able to carry out various types of transactions via a smartphone or computer or from the bank, which can save operational costs. This study was conducted to determine the level of use of E-Banking during the Covid-19 pandemic among UPNVJ students. To support this final project to be more perfect, very accurate data is needed. The data collection technique used in this research is by using the questionnaire method. Technical analysis of the data using a descriptive discussion. From the results of the research conducted, it can be concluded that the use of E- Banking among UPNVJ students increased during the Covid-19 pandemic compared to before the Covid-19 pandemic. E-Banking products can provide convenience and security for customers of a bank in conducting transactions during the Covid-19 pandemic which requires to keep a distance so that the transmission of the Covid-19 virus does not occur, namely because E-Banking can be used anytime and anywhere without having to come. directly to the bank.